2016
DOI: 10.1038/modpathol.2015.144
|View full text |Cite
|
Sign up to set email alerts
|

High-definition CpG methylation of novel genes in gastric carcinogenesis identified by next-generation sequencing

Abstract: Gastric cancers are the most frequent gastric malignancy and usually arise in the sequence of Helicobacter pylori-associated chronic gastritis. CpG methylation is a central mechanism of epigenetic gene regulation affecting cancer-related genes, and occurs early in gastric carcinogenesis. DNA samples from non-metaplastic gastric mucosa with variable levels of gastritis (non-metaplastic mucosa), intestinal metaplasia, or gastric cancer were screened with methylation arrays for CpG methylation of cancer-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…In addition to studies from Asian populations, one study came from the Caucasian population. The results of this study showed that the CHFR methylation was significantly increased in gastric cancer compared with non-metaplastic mucosa 28. Taken together, these data showed a parallel effect of CHFR methylation on gastric cancer risk among different ethnicities.…”
Section: Discussionsupporting
confidence: 63%
“…In addition to studies from Asian populations, one study came from the Caucasian population. The results of this study showed that the CHFR methylation was significantly increased in gastric cancer compared with non-metaplastic mucosa 28. Taken together, these data showed a parallel effect of CHFR methylation on gastric cancer risk among different ethnicities.…”
Section: Discussionsupporting
confidence: 63%
“…CIMP GCs tended to harbor mutations in the oncogenes CTNNB1 , ERBB2 , KRAS , and PIK3CA 74 . Similarly, reduced expression of hypermethylated BRINP1 , SGCE, and MLH1 was significantly associated with favorable survival in GC 75 . Moreover, infectious agents such as H pylori , EBV, and the infection-associated inflammatory response all induce altered DNA methylation 76, 77, 78.…”
Section: Molecular Genetic Profiling Of Gastric Cancermentioning
confidence: 99%
“…The literature reports many genes significantly hypermethylated in cancer tissue compared with normal tissue of GC subjects [1820], but relatively few studies have reported DNA methylation markers for early detection [2124]. Furthermore, quantification of global 5-methylcytosine content [25] and evaluation of long interspersed nuclear elements (LINEs) by Lee [26] and others have emphasized the importance of global DNA hypomethylation in GCs, although little is known about its role in GC.…”
Section: Introductionmentioning
confidence: 99%